Causal relationship among critical factors for cellular manufacturing system using DEMATEL approach. (4th March 2022) - Sharma, Vikrant; Gidwani, B.D.; Sharma, Vikram; Meena, M.L.
The purpose of this research paper is to visualise the prioritisation and interrelationships among essential factors of cellular manufacturing system (CMS) implementation in a manufacturing firm located in India using the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method. Based on the literature review, 17 CM factors were identified which were validated by experts. A questionnaire was created that was replied by five experts serving within the firm. Then, the DEMATEL technique was applied to clarify the complicated relationship between essential factors and evaluate their key influences. The main contribution of this study is to identify and prioritise the factors that managers are facing in CMS implementation. The result of this study indicates that training is an essential factor for the CM implementation. The strength of the present study is that it is one of the first few to be conducted in perspective for CM implementation factors analysis.